2020
DOI: 10.1186/s12915-020-00875-4
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and pharmacogenomic risk stratification in the United States

Abstract: Background Pharmacogenomic (PGx) variants mediate how individuals respond to medication, and response differences among racial/ethnic groups have been attributed to patterns of PGx diversity. We hypothesized that genetic ancestry (GA) would provide higher resolution for stratifying PGx risk, since it serves as a more reliable surrogate for genetic diversity than self-identified race/ethnicity (SIRE), which includes a substantial social component. We analyzed a cohort of 8628 individuals from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Although it has been shown that self‐identified race ethnicity and genetic ancestry are highly concordant for PGx risk stratification, 48 we evaluated the ancestry composition of participants among self‐reported race groups to confirm these findings in our cohort prior to conducting the PGx assessment. Whereas the predominant ancestry fraction among each self‐reported race group was concordant, we present examples where the use of self‐reported race in lieu of PGx testing for variants that are thought to be unique to a specific ancestry group, may fail to identify participants who harbor the variant due to genetic admixture.…”
Section: Discussionmentioning
confidence: 88%
“…Although it has been shown that self‐identified race ethnicity and genetic ancestry are highly concordant for PGx risk stratification, 48 we evaluated the ancestry composition of participants among self‐reported race groups to confirm these findings in our cohort prior to conducting the PGx assessment. Whereas the predominant ancestry fraction among each self‐reported race group was concordant, we present examples where the use of self‐reported race in lieu of PGx testing for variants that are thought to be unique to a specific ancestry group, may fail to identify participants who harbor the variant due to genetic admixture.…”
Section: Discussionmentioning
confidence: 88%
“…In this sense, the Spanish population is very homogeneous between the different Spanish regions, and it has been described as similar to other European populations but more genetically diverse than Western and Northern Europeans [20]. This fact is mainly due to the fraction of North-West African ancestry (0-11%) in Spanish population, related to an admixture event occurring during the Muslim rule in Iberia [21]. Of note, we have already observed these differences in the Spanish population [22].…”
Section: Introductionmentioning
confidence: 99%
“…Given that individuals of other biogeographical ancestries are known to have different clozapine pharmacokinetic profiles 9 , our study cannot assess a potential rare variant contribution to those known ancestral differences, and its results might not be straightforwardly transferrable to non-European populations. We note, however, that consistency of variant effect sizes across populations is a reasonable assumption for pharmacogenes 52 and that the occurrence of deleterious variation in these gene sets is frequent (though individually rare) across continental ancestries 53 . Thus, the association between rare damaging burden and clozapine metabolism identified here could be of relevance beyond the European sample in which it was discovered.…”
Section: Discussionmentioning
confidence: 79%